Legal aspects of health implications caused by environmental distress - Knez, Rajko (Medicine, law & society, 2017)
The article tries to explore legal consequences in cases where the environmental distress causes health implications for individuals. The author begins with the observations from two different angles, that is ex ante and ex post actions. Both approaches differ substantively, since the ex ante approach is applied by state authorities (command-and-control approach, de iure imperii acts), while the ex post approach is by a general rule initiated by individuals against polluters/state. Both approaches are discussed considering the application of EU rules and beyond (ECHR, Aarhus convention). The main emphasis is given to one of the biggest problems, that is the issue of causality, which discourages many plaintiffs from claiming damages. For the so-called post-industrial risks the conventional rules of causality do not suffice, which is why certain courts proposed that changes in this respect are necessary. In addition, the role of NGOs is emphasised, since the NGO can, especially in the ex ante approach, achieve better effects, especially when locus standi is assured.
Keywords: claims for damages; command-and-control approach; ECHR Art. 2; ECHR Art. 8; environmental protection; health; healthy living environment; legal remedies in environmental law